Structure and stability of kaolinite/TiO2 nanocomposite: DFT and MM computations - Tokarský, Jonáš; Capková, Pavla; Burda, Jaroslav V (Journal of molecular modeling, 2012)
The adhesion of TiO(2) (anatase structure) nanoparticles to kaolinite substrate was investigated using molecular modeling. Universal force field computation, density function theory computation, and a combination of both two approaches were used. This study enabled the adhesion energy for the TiO(2)/kaolinite nanocomposite to be estimated, and revealed the preferred orientation of the TiO(2) nanoparticles on the kaolinite substrate. The results of all three levels of computation were compared in order to show that the accuracy of universal force field computations is sufficient in this context. The role of nanoparticle size and the importance of the nanoparticle-substrate bonding contribution are presented here and discussed. A comparison of the molecular modeling results with scanning electron microscopy observations showed that the results of the modeling were consistent with the experimental data, and that this approach can be used to help characterize nanocomposites of the nanoparticle/phyllosilicate substrate type.
Keywords: povrchové vlastnosti; Particle Size; Thermodynamics; Nanoparticles; kaolin; titan; Computer Simulation; nanočástice; Crystallography; Titanium; kvantová teorie; nanokompozity; molekulární modely; molekulární konformace; Nanocomposites; Models, Molecular; termodynamika; Kaolin; krystalografie; velikost částic; Surface Properties; počítačová simulace; Molecular Conformation; Quantum Theory